Structures of ethanol spray flames under CO2 dilution of the oxidizer in the counterflow configuration under MILD combustion conditions - Noreña, Oscar; Gutheil, Eva (Fluids, 2020)
Structures of both gaseous and liquid ethanol flames in different oxidizing gas environments in the axisymmetric counterflow configuration at atmospheric pressure are studied. Initially, ethanol/air gas flames are considered where pure ethanol is directed against air at initial temperatures of 400 K, and N2 is successively removed to obtain structures of ethanol/O2 gas flames. Furthermore, the addition of CO2 to the oxidizer side is carried out. Then, an ethanol spray is carried by air and directed against an air stream, and the same procedure is performed as described for the gas flames. The gas strain rate at the fuel side of the configuration is increased from low values of 55/s up to extinction, and the initial droplet diameter is varied. For the combustion of gaseous ethanol in air and in pure oxygen, the nitrogen removal results in an increase in the maximum flame temperature from 2010 K to 2920 K at a gas strain rate of 55/s on the fuel side of the configuration, and the extinction strain rates are 630/s and 26,000/s, respectively. It is confirmed that ethanol spray flames in air show two reaction zones at low strain whereas the lean ethanol spray flames in pure oxygen exhibit a single reaction zone in all situations studied. For increased liquid fuel mass flow rate to a global equivalence ratio of unity, two reaction zones are retrieved. An analysis regarding the addition of CO2 in both the ethanol/oxygen gas and spray flames is also discussed and is found that CO2 dilution of the carrier gas the spray is much more efficient than diluting the opposed gas stream in the counterflow configuration for the generation of MILD combustion conditions in oxy-fuel flames.
Im Titel ist die Zahl 2 bei CO2 tiefgestellt
Gesehen am 29.04.2024